Psychosocial assessments for young people: a systematic review examining acceptability, disclosure and engagement, and predictive utility - Bradford S; Rickwood D (Dove Medical Press, 2012)
Sally Bradford,1 Debra Rickwood1,21Faculty of Health, University of Canberra, Canberra, 2Headspace National Youth Mental Health Foundation, North Melbourne, AustraliaAbstract: Adolescence and young adulthood are often turbulent periods in a person’s life. There are high rates of accidental deaths, suicide, mental health concerns, substance use, and sexual experimentation. Health care professionals need to conduct holistic assessments of clients in these developmental life stages to identify psychosocial risks and provide targeted early intervention and implement prevention strategies. The most useful psychosocial assessments for most health care professionals are those that can provide a complete picture of the young person’s life and circumstances. This article identifies psychosocial assessment instruments that can be used as an initial assessment and engagement tool with the general population of young people presenting for health care. We review the psychometric properties of each of the instruments, determining what type of instrument is most acceptable to young people, whether any can increase disclosure and improve engagement between young people and health professionals, and whether they have predictive utility. The search strategy complied with the relevant sections of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A total of 89 published articles were identified, covering 31 different assessment instruments. Results indicated that those that were self-administered were most acceptable to young people, although it is unclear whether pen-and-paper or computer formats were preferred. Most psychosocial assessments can improve rates of disclosure and enhance engagement between young people and health professionals; however, worryingly, we found evidence that clinicians did not always respond to some of the most serious identified risks. Only for one instrument was there any mention of predictive utility. Future research should employ longitudinal approaches to determine the predictive utility of psychosocial assessments and focus on whether the use of new technologies can improve rates of disclosure.Keywords: adolescence, emerging adults, mental health, intervention, prevention, risk